Methods of bud propagation - Smith, William Elmer (My University, 1893)
Introduction: One of the marked and strongly stamped characteristics of man, is his constant and ungratifying desire for variation. Mortal beings are not content to use the same thing always; to travel in the same old rugged path; there must be a change, however small, or in whatever direction it takes.
Citation: Smith, William Elmer. Methods of bud propagation. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Man; Variation; Change; Theses; Manuscripts (documents)